1973
DOI: 10.1063/1.1654972
|View full text |Cite
|
Sign up to set email alerts
|

Formation of vanadium silicides by the interactions of V with bare and oxidized Si wafers

Abstract: Formation of vanadium silicides by the interactions of vanadium with bare and oxidized Si wafers has been studied by both x-ray diffraction and He ion backscattering techniques. X-ray diffraction was used to identify phases and ion backscattering to profile compositional changes. In the case of V on Si, the silicide VSi2, which is a silicon-rich phase, was found to form at temperatures from 600 to 1000 °C. In the case of V on SiO2, reactions took place only at temperatures above 800 °C, and the reaction produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…In contrast to Tu et al, 3 we observe a linear reaction rate for the silicide formation on Si, but oxygen is shown to decelerate the reaction noticeably. The resulting silicide layer has the composition VSi 2 • On Si0 2 substrates, the growth rate of the silicide layer is proportional to (time)…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast to Tu et al, 3 we observe a linear reaction rate for the silicide formation on Si, but oxygen is shown to decelerate the reaction noticeably. The resulting silicide layer has the composition VSi 2 • On Si0 2 substrates, the growth rate of the silicide layer is proportional to (time)…”
Section: Introductioncontrasting
confidence: 53%
“…We have measured the rate of growth of the intermediate V 3 Si layer (b) as a function of anneal time at various temperatures. The result is given in Fig.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the phase diagram, (1) there are four distinct solid compounds in (vanadium + silicon); namely, V 3 Si, V 5 Si 3 , V 6 Si 5 , and VSi 2 . Only V 3 Si has a significant range of composition, and V 6 Si 5 appears to be stable only at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been found that silicide layers are formed during heat treatment of metal layers on Si02. 11 • 16 Usually, a different phase is formed and the reaction temperature is 100-200°C higher than for the metal-silicon systems.…”
Section: Introductionmentioning
confidence: 99%